Emerging Topical and Systemic JAK Inhibitors in Dermatology - Solimani, Farzan; Meier, Katharina; Ghoreschi, Kamran (Frontiers in Immunology, 2019)
The accumulating knowledge on cellular and molecular pathways helps to develop novel therapeutic strategies in skin inflammation and autoimmunity. Examples are psoriasis and atopic dermatitis, two clinically and immunologically well-defined disorders. Here, the elucidation of crucial pathogenetic factors such as IL-17A/IL-23 on the one hand and IL-4/IL-13 on the other hand profoundly changed our therapeutic practice. The knowledge on intracellular pathways and governing factors is shifting our attention to new druggable molecules. Multiple cytokines and their receptors rely on the ability of a small family of four proteins called Janus kinases (JAKs) and their associated signal transducer and activators of transcription (STAT) molecules. Inhibition of these proteins can simultaneously block multiple cytokines. Therefore, JAK inhibitors (JAKi) are emerging as a new class of drugs, which in dermatology can be used systemically as oral drugs or topically in different cream formulations. Inhibition of these molecules has been shown to be effective in various skin disorders. The first oral JAKi have been recently approved for the treatment of rheumatoid arthritis and psoriatic arthritis. Currently, multiple inhibitors of the JAK/STAT pathway are being investigated for skin diseases like alopecia areata, atopic dermatitis, dermatomyositis, graft-versus-host-disease, lichen planus, hidradenitis suppurativa, lupus erythematodes, psoriasis vulgaris and vitiligo. Here, we aim to discuss the immunological basis and current stage of development of JAKI in dermatology.